Neuro-opthalmological and neuro-surgical aspects of papilledema - V. A. Vasyuta; V. V. Biloshytsky; L. D. Pichkur; A. P. Huk; O. Yu. Malysheva; L. R. Borovyk (Journal of Ophthalmology, 2020)
Papilledema is optic disc swelling that is secondary to elevated intracranial pressure. Possible conditions causing high intracranial pressure and papilledema include brain neoplasms, head trauma, hydrocephalus, and other disorders of the central nervous system. Papilledema is diagnosed using ophthalmoscopy and/or neuroimaging. The differential diagnosis includes pseudopapilledema and inflammatory and vascular disorders of the optic disc. The treatment is aimed at reducing the intracranial pressure of the patient.